2013 Elijah High Altitude Balloon Payload Team - Cybela, Trent; Kass, Daniel; Koeune, Amber; Pedigo, Nathaniel; Tirimacco, Alana (Proceedings of the Wisconsin Space Conference, 2014)
Over the past ten weeks, the payload team for the Elijah High Altitude Balloon Project has researched, designed, and constructed a scientific payload that would fly to the edges of space and gather data advancing the teamâ€™s knowledge of Earth sciences, aerospace sciences, and aerospace engineering. The payload packages consisted of a sensor suite, telemetry system, Geiger counter, and camera. The telemetry system was able to provide a live data feed that interacted with existing networks to record data acting as a proof of the concept that a similar system would be viable and even suggested for future teams. The sensor suite was designed to gather data that would provide tracking data and finalize the battery experiment. While the tracking sensors were unsuccessful the thermistors and voltmeter reported data that confirmed that the various electronic components onboard were kept within their operating temperatures and gave data on the battery performance inflight. The Geiger counter data that was gathered was not able to be directly correlated with an altitude, it was able to be correlated with time, and as all data points received were on the ascent of the balloon it is possible to state that there was a positive correlation between radiation levels and altitude. The camera system that was included in the payload was able to record the entirety of the two flights and provided imagery from the edge of space. A large amount of the project was also devoted to the development of a rugged and reusable capsule; this task was accomplished by the creation of a layered capsule wall that insulated the capsule and gained increased rigidity due to the geometry of the capsule and an internal rib cage that supported plates for the electronics.Â 